Attitudes And Environmental Knowledge Of Damascus University Students Field Study Comparative A (Damascus University Journal of educational and Psychologyical sciences, 2021)
The research aims to know attitudes and environmental knowledge of Damascus University students. The  sample consisted of (512) male and female, and detected the differences between them according to the variables: sex, discipline  of the study( science disciplines/ theoretical disciplines), studying stage( junior/ senior) classes, their preferences  of literary and media  devices, economic level of the family, and the kind of parents job. The researcher  modified the   scale of attitudes and ecological knowledge (Maloney, Ward & Braucht, 1975) into local environment,  which consists of four subscales ( verbal commitment, actual commitment, emotion, and knowledge).The most important results were : the females were  more verbal commitment  and emotionally with the environment than males, the senior classes students were more emotional  than junior classes. The students of low family economic level had more environmental knowledge  than those of high level one.There was a significant positive  effect of  internet  and reading books on environment knowledge of the students. Finally there wasn`t  a significant effect of the kind of parents' job  on students environmental  attitudes and knowledge.
Keywords: Environmental Attitudes; Environmental Knowledge; Verbal Commitment, Actual Commitment; Affect; Reasoned Action; Planned Behavior; Intention